Magnetic structuring of linear copper electrodeposits - ACKLAND, KARL; COEY, JOHN (My University, 2012)
Electrodeposition of copper is investigated in localized magnetic fields produced by linear arrays of permanent magnets. The thickness and texture of the deposits depend on the magnitude and direction of the field. The deposition rate is explained in terms of magnetic pressure on the diffusion layer. Addition of non-electroactive GdCl 3 to the electrolyte inverts the structuring of the electrodeposits, producing thick dendritic growth in regions where the field is smallest.
PUBLISHED
Keywords: Physics